PEMBERDAYAAN DAN KINERJA PENGURUS BADAN USAHA MILIK DESA KECAMATAN MEGAMENDUNG KABUPATEN BOGOR - Herman Herman; Sri Hartini (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2019)
This study aims to describe employee empowerment both in total and dimension, describe employee performance in both total and dimension, and the relationship of empowerment to the performance of the administrators of Village Owned Enterprises (BUM Desa) in Megamendung District, Bogor Regency. This research was designed using quantitative descriptive research. The subject of this research is the management of the Village-Owned Enterprises (BUM Desa) sub-district of Megamendung, Bogor Regency as many as 23 people, while the object is the empowerment and performance of employees. Data were collected using a questionnaire. Data were analyzed descriptively and correlatively using SPSS 23. The results showed that there were a relationship between empowerment and employee performance. There is a very strong relationship between empowerment and performance among BUM Desa employees in Megamendung, Bogor Regency. The implications of this research can be an important input for BUM Desa administrators to increase employee involvement in order to improve the performance of BUM Desa administrators in Megamendung District so that they can achieve high competitiveness.